Intrava DX Tank Mixtures for Weed Control in Corn - Patrick W. Geier; Sarah H. Lancaster (Kansas Agricultural Experiment Station Research Reports, 2025)
Intrava DX is a new premix herbicide for potential use in fallow and corn. Data from Manhattan showed Intrava DX provided exceptional (≥ 95%) weed control of key weed species when applied preemergence (PRE) to corn. Corn injury was less than 6%, and no difference was observed in grain yield. At Garden City, most Intrava DX treatments provided greater than 90% visual weed control throughout the season. Weed densities were reduced by more than 90%, and grain yields were 3.8 to 4.2 times higher when corn received Intrava DX compared to the weedy controls. Intrava DX may be an important component of an integrated weed management system to combat resistance.
Keywords: residual control; resistance management